(untitled) (Journal of Science & Technology, 2021)
The article discusses the industry adoption and best practices in defect prediction models, emphasizing their integration, collaboration, explain ability, continuous improvement, and alignment with organizational goals. It outlines key practices such as integration into development workflows, collaboration between data scientists and developers, explain ability for developer understanding, continuous model evaluation, addressing imbalanced datasets, context-aware model configuration, training on representative data, feedback loops for continuous improvement, rigorous model evaluation metrics, and alignment with organizational goals. These metrics provide quantitative insights into code quality and defect proneness. Defective software modules cause software failures, increase development and maintenance costs, and decrease customer satisfaction. These practices collectively enable organizations to proactively manage software quality, improve development workflows, and deliver reliable software solutions. In addition, the case studies presented showcase the real-world application and impact of defect prediction models in diverse industries. Numerous software quality models have been proposed and developed to assess and improve the quality of software products.The cases include a large-scale e-commerce platform achieving a 20% reduction in post-release defects, a software development consultancy improving resource allocation efficiency by 15%, an open-source software community experiencing a 30% reduction in the time taken to address defects, and a financial services organization achieving a 25% reduction in security-related defects. Lessons learned from these case studies highlight the importance of tailoring to context, continuous feedback loops, integration into workflows, metric selection, transparency, and collaboration in maximizing the effectiveness of defect prediction models across various development contexts.